Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1017/s0033291717002902
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of MATRICS Consensus Cognitive Battery scores in a large sample of outpatients with schizophrenia and their unaffected relatives

Abstract: In a large sample of stable patients with schizophrenia, living in the community, and in their unaffected relatives, MCCB demonstrated sensitivity to cognitive deficits in both groups. Our findings of significant within-family prediction of MCCB scores might reflect disease-related genetic or environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 62 publications
7
36
0
Order By: Relevance
“…The exclusive involvement of the academic domain in relatives, already reported by other authors (4,5), could be related to a mild cognitive dysfunction that has been described by several authors (68)(69)(70)(71)(72)(73) and found in the sample of relatives recruited in the present multicenter study (63,74).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The exclusive involvement of the academic domain in relatives, already reported by other authors (4,5), could be related to a mild cognitive dysfunction that has been described by several authors (68)(69)(70)(71)(72)(73) and found in the sample of relatives recruited in the present multicenter study (63,74).…”
Section: Discussionsupporting
confidence: 75%
“…Data analysis. Co-norming and standardization of the Italian MCCB test scores was carried out as described in Kern et al (55,63). For cognitive domains including more than one measure, that is working memory and speed of processing, the summary score for the domain was calculated by summing the scores of the tests included in that domain and then standardizing the sum to a Tscore.…”
Section: Assessmentsmentioning
confidence: 99%
“…However, there may be intercultural differences in social processes and it would be interesting to examine these intercultural differences in social cognitive processes in patients with schizophrenia. Also, environmental factors [41,42], dietary influence [43,44] or stress-induced lifestyle condition may influence brain function and future studies may want to investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…The components of mental health proposed by the authors are identified on the basis of a wide literature. Cognitive and social skills impact on all aspect of everyday life [16], and are considered to be impaired in sev-eral mental disorders ( [17][18][19]. The ability to recognize, express and modulate one's own emotions is also related both to mental health and to mental disorders [20].…”
Section: Searching For Normative Criteriamentioning
confidence: 99%